Prevalence and risk factors for stroke in a population of Southern Brazil Prevalência e fatores de risco para AVC numa população do sul do Brasil - Leslie Copstein; Jefferson Gomes Fernandes; Gisele Alsina Nader Bastos (Arquivos de Neuro-Psiquiatria)
Stroke is the leading cause of death in many countries of Latin America. Population studies are necessary in this region. Objectives: To evaluate the prevalence of stroke and its risk factors in a population of vulnerable communities of southern Brazil. Methods: Population-based crosssectional study with systematic sampling. Individuals aged 20 and over were included (n=3,391). Individuals with previous diagnosis of stroke or identified by a validate stroke questionnaire were compared with those without stroke in many variables. Results: 285 individuals (8.4%) had previous stroke. The group without stroke showed greater average of years of study than the group with stroke (p≪0.001). Multivariable analysis identified as risk factors for stroke (p≪0.05): age from 40 to 59, age from 60 to 79, widowhood, present smoking, previous smoking, hypertension and ischemic heart disease. Conclusion: The findings in this population indicate the need of preventive cost-effective public health policies in Brazil. O acidente vascular cerebral (AVC) é a principal causa de morte em muitos países da América Latina. Objetivos: Avaliar prevalência e fatores de risco para AVC em população de comunidades vulneráveis no sul do Brasil. Métodos: Estudo transversal de base populacional com amostragem sistemática. Foram incluídos os indivíduos a partir de 20 anos de idade (n=3.391). Indivíduos com prévio diagnóstico de AVC ou identificados por questionário validado para AVC foram comparados àqueles sem AVC em diversas variáveis. Resultados: 285 indivíduos (8,4%) referiram AVC prévio. O grupo sem AVC teve maior média de anos de estudo que o grupo com AVC (p≪0,001). Foram identificados como fatores de risco para AVC (p≪0,05): idade de 40 a 59 anos, idade de 60 a 79 anos, viuvez, tabagismo no presente, tabagismo no passado, hipertensão arterial sistêmica e doença isquêmica do coração. Conclusão: São necessárias no Brasil políticas de saúde pública preventivas e custo-efetivas.